An analysis of multicultural values: empirical study on students at Universitas Muhammadiyah Gombong - Tian Khusni Akbar; Deni Setiyawan; Sovi Sulhana; Novi Wahyuni; Furkotriningsih Furkotriningsih; Dita Uswatun Hasanah (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
This study aims to examine the values of multiculturalism in students at Muhammadiyah Gombong University both theoretically and practically, in the context of everyday life. The research was motivated by the plurality (ethnicity, race, culture, language and religion) of different students which raises concerns in social aspects and academic communities. A survey was conducted on 250 students from 6 study programs of the Faculty of Health Sciences, Muhammadiyah University of Gombong to obtain data on multicultural values in the campus environment. The method used was mixed methods to collect quantitative (numerical) and qualitative (descriptive) data. The results showed that multiculturalism lies in the attitude of openness, active acceptance, and equal recognition of social groups as an integral part of an entity Society, both democratic values, harmony and tolerance. The Strategy of Muhammadiyah Gombong University in Building Multicultural values includes 3 ways, namely the Role of Student Organizations and UKM, Collaboration of lecturers and students, and the Role of the Curriculum as a Container for Multicultural Character Building. Overall, this research concludes that Muhammadiyah Gombong University strengthens the position of successful Islamic higher education as a strategic space for inclusive and transformative multicultural character building.